2021
DOI: 10.21203/rs.3.rs-310699/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perceived and Actual Risks of Drought : Household and Expert Views From Lower Teesta River Basin of Northern Bangladesh

Abstract: Disaster risk perception, as well as risk appraisal, play a pivotal role in making the disaster risk reduction policy. This study examines the actual vs perceived drought risks by constructing risk indices at the household and expert levels using survey data from the lower Teesta River Basin in northern Bangladesh. Survey data were collected from 450 farmers based on the structural questionnaire. A composite drought risk index was developed to understand households’ perceived and actual risks in the designated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…Interestingly, past experiences of facing drought, earthquake, and ood hazards didn't show any signi cant correlation with the dependent variables which regulate the severity of disaster risk. The present study found that the female respondents perceived more risks, lack enough knowledge, and will be less capable of controlling the upcoming disasters than male which is supported by the ndings of Salam et al (2021). Adequate measures need to be taken to reduce the gap of risk perception between male and female.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Interestingly, past experiences of facing drought, earthquake, and ood hazards didn't show any signi cant correlation with the dependent variables which regulate the severity of disaster risk. The present study found that the female respondents perceived more risks, lack enough knowledge, and will be less capable of controlling the upcoming disasters than male which is supported by the ndings of Salam et al (2021). Adequate measures need to be taken to reduce the gap of risk perception between male and female.…”
Section: Discussionsupporting
confidence: 66%
“…In a short term, the progression of collection, selection, and interpretation of the impacts of certain unpredictable events denote RP (Wachinger, 2013;Castro et al, 2017). Most scholars do believe that commons RP can in uence their preparedness for, response to, and recovery from natural disasters (Grothmann and Reusswig, 2008;Ho et al, 2008;Salam et al, 2021). RP plays a vital role in managing any hazardous and disastrous event.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Even after the great ood in northern Bangladesh in August 2017, there found no notable research on ood RP (Islam and Haque, 2018). Previous studies on RP conducted in north-western Bangladesh considering in single risk perspective of drought (Habiba et al, 2012, Salam et al, 2021, Earthquake (Islam et al, 2016), Riverbank erosion (Alam et al, 2017), and ood risk (Rahman, 2017). However, the integrated RP studies of drought, earthquake, and ood are still unexplored in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%